2014
DOI: 10.3389/fmicb.2014.00199
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to high salt concentrations in halotolerant/halophilic fungi: a molecular perspective

Abstract: Molecular studies of salt tolerance of eukaryotic microorganisms have until recently been limited to the baker's yeast Saccharomyces cerevisiae and a few other moderately halotolerant yeast. Discovery of the extremely halotolerant and adaptable fungus Hortaea werneckii and the obligate halophile Wallemia ichthyophaga introduced two new model organisms into studies on the mechanisms of salt tolerance in eukaryotes. H. werneckii is unique in its adaptability to fluctuations in salt concentrations, as it can grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
101
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 78 publications
4
101
1
Order By: Relevance
“…As far as we known, among these genera only Alternaria was previously identified in natural hypersaline environments (GundeCimerman et al 2009;Wang et al 2013;Gunde-Cimerman and Zalar 2014). These variations in the salt tolerance may be attributed to the different mechanisms of tolerance exhibited by different isolates (Plemenitaš et al 2014). Tolerance to NaCl also decreased with incubation time, which suggested that toxicity of NaCl increased with incubation time.…”
Section: Discussionmentioning
confidence: 99%
“…As far as we known, among these genera only Alternaria was previously identified in natural hypersaline environments (GundeCimerman et al 2009;Wang et al 2013;Gunde-Cimerman and Zalar 2014). These variations in the salt tolerance may be attributed to the different mechanisms of tolerance exhibited by different isolates (Plemenitaš et al 2014). Tolerance to NaCl also decreased with incubation time, which suggested that toxicity of NaCl increased with incubation time.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of glycerol are increased with increasing salinity and decreased after hy-poosmotic shock (51,52). Several genes known to be involved in glycerol production were found in the genomes of H. werneckii and W. ichthyophaga (53). Among these genes, there are three aquaglyceroporin homologues corresponding to AgglpF.…”
Section: Discussionmentioning
confidence: 99%
“…In S. pombe the putative sensors are cytoplasmic and have PAS domains, identified in oxygen and redox sensing in bacteria (Gacto et al 2003;Bahn 2008). Cytoplasmic osmosensors have also been recently identified in the highly halotolerant yeasts Debaryomyces hansenii (DhNik1) and Hortaea werneckii (Meena et al 2010;Plemenitas et al 2014). D. hansenii's osmosensor is a group III HK, characterized by having HAMP domain repeats with no transmembrane domains; deletion analysis has shown that interaction among the HAMP repeats could function as an on-off switch during the osmotic stress response (Meena et al 2010).…”
Section: Yeast and Fungimentioning
confidence: 98%
“…Since there are excellent reviews for yeast osmosensing and regulation (Saito 2001;Santos and Shiozaki 2001;O'Rourke et al 2002;Gacto et al 2003;Westfall et al 2004;Hohmann et al 2007;Bahn 2008;Plemenitas et al 2014) we will cover this group for comparison.…”
Section: Introductionmentioning
confidence: 99%